Mechanical characterization of steel fibre reinforced acrylic emulsion polymer modified concrete - Hazimmah, S. D. S.; S., Mohd; Cheng, Hock Tian (Medwell Journals, 2011)
A comparative study between acrylic emulsion Polymer Modified Concrete plain (PMC), reinforced with steel fibres (SFRPMC), Steel Fibre Reinforced Concrete (SFRC) and plain concrete was made. The fibres are 60 mm long and the fibre content was 0.010, 0.015 and 0.020%, respectively in volume. The steel fibres reinforcement was randomly dispersed into the matrix of acrylic emulsion polymer modified concrete. An increase in mechanical properties was observed as function of reinforcement and in addition of acrylic emulsion polymer. The comparison also showed that polymer modified concrete, plain and reinforced has a better performance than regular market concrete, suggesting that acrylic emulsion polymer modified concrete is a reliable alternative for construction industry.